Relación entre variables sociodemográficas, patogénicas y salutogénicas, con la calidad de vida en estudiantes universitarios colombianos - Riveros, Fernando; Vinaccia-Alpi, Stefano (Revista de Psicopatología y Psicología Clínica, 2017)
Abstract: Relationship between sociodemographic, pathogenic and salutogenic variables and the quality of life of Colombian university students. Several studies have analyzed the quality of life related to health, but few in healthy population, ignoring its predictive variables. The objective of this research was to evaluate the relationship between sociodemographic, pathogenic and salutogenic variables, and health-related quality of life (HRQOL). Five hundred and three university students of 17 Colombian universities participated in the study. Several instruments related to the study variables were applied. The results showed: (1) High scores in HRQOL, anxiety, perceived stress, resilience and optimism, and low scores in depression; (2) inverse relationship between HRQOL and anxiety, depression and perceived stress; (3) inverse relationship between vitality and depression and perceived stress; (4) optimism showed a direct relationship to the mental component of quality of life; (5) higher scores for men in HRQOL and resilience, and for anxiety in women; and (6) the mental health component in men is explained by perceived stress and depression, whereas in women it is explained by perceived stress, depression, anxiety and the current semester. In conclusion, HRQOL scoring is mainly associated with pathogenic variables. Resumen: Varios estudios han analizado la calidad de vida relacionada con la salud, pero pocos en población sana, desconociendo sus variables predictoras. El objetivo de este estudio fue evaluar la relación entre variables sociodemográficas, patogénicas y salutogénicas con la calidad de vida relacionada con la salud (CVRS). Participaron 503 universitarios de 17 universidades colombianas a los que se les aplicó diversos instrumentos relacionados con las variables de estudio. Los resultados mostraron: (1) Altas puntuaciones en CVRS, ansiedad, estrés percibido, resiliencia y optimismo, y bajos niveles de depresión; (2) relaciones inversas entre ansiedad, depresión y estrés percibido con CVRS; (3) relaciones inversas entre depresión y estrés percibido con vitalidad; (4) el optimismo mostró una relación directa con el componente mental de calidad de vida; (5) mayores puntuaciones para hombres en CVRS y resiliencia, y para ansiedad en mujeres y (6) el componente de salud mental en hombres, lo explica el estrés percibido y la depresión, mientras que en mujeres lo explica el estrés percibido, depresión, ansiedad y semestre en curso. Puede indicarse que las puntuaciones en CVRS están asociadas principalmente a variables patogénicas.